2009
DOI: 10.1097/cej.0b013e3283307770
|View full text |Cite
|
Sign up to set email alerts
|

Life after childhood cancer: marriage and offspring in adult long-term survivors – a population-based study in the Piedmont region, Italy

Abstract: The majority of childhood cancer cases survive to adulthood. We describe the experience of marriage and reproduction as indicators of quality of life, in a population-based cohort of adult long-term survivors after early cancer reported to the Childhood Cancer Registry of Piedmont. The study included 1237 survivors with a malignant neoplasm diagnosed during 1967-2000 when aged 0-14 years, who attained age 18 years. Vital and marital status and number of offspring were assessed through the Vital Statistics Offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 33 publications
4
17
0
Order By: Relevance
“…These findings are in accordance with previous studies in Piedmont, 13,20 and Wales. 11 They confirm that, in some aspects, the social life of these subjects retains some significant difference, or even limitations, in comparison with that of their peers.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are in accordance with previous studies in Piedmont, 13,20 and Wales. 11 They confirm that, in some aspects, the social life of these subjects retains some significant difference, or even limitations, in comparison with that of their peers.…”
Section: Discussionsupporting
confidence: 83%
“…38 In this study, there was a significant excess of male offspring that persisted also after adjusting for birth order. This finding is consistent with those of previous studies conducted in Piedmont 13,20 (the Piedmont cohort is included in the present study and represents 9.7% of the OTR cohort) but has not been observed in other studies. [39][40][41][42][43][44] We can speculate that a wider use of assisted reproduction treatments, which are known to influence the gender ratio of children, might explain this finding.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In an earlier Italian study, there was a reported fertility deficit of 41%. 7 In Finland, only 15% of survivors parented at least one child compared to 58% of siblings. 8 The British Childhood Cancer Survivor Study reported only 31% of survivors having at least one child which is approximately two-thirds of what would be expected from British population statistics.…”
mentioning
confidence: 99%
“…On average, the wedding rate of survivors of childhood cancer is 32% lower than that of the general population for men and 18% lower for women. The discrepancy is very sharply marked for survivors of brain tumors, who are affected by endocrine and neurological complications as well as emotional disorders (Dama 2009). …”
Section: Fecundity Of Survivors Of Childhood Cancermentioning
confidence: 99%